Alternatif Steam untuk Pembelajaran Matematika di SD Abad Ke-21 (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Mastery of science and technology is a must in facing the era of globalization. This requires various parties to be able to develop capabilities related to the development of capabilities in the field of technology. In the field of education, one of the educational breakthroughs in Indonesia that seeks to develop humans who can create a science and technology-based economy is STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning. This study aims to describe STEAM as an alternative to learning mathematics in SD in the 21st century. This study uses a literature review method. The library study method is a critical study of the discussion of a topic that has been written by researchers or scientists in various sources in the form of books, journals, ebooks, or other scientific articles. The results of this study indicate that it is very important to use learning methods and media in the world of education to support teaching and learning activities, especially at the SD level. STEAM is one of the methods that can be used in learning but it is undeniable that this method cannot be applied in all school circles. Schools that have been able to use this method are those that are well-coordinated. Therefore, we really hope that this STEAM method can be implemented in all school circles which also indicates that our education is developing to be better every day.